2006
DOI: 10.1080/01485010600664032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Anomalies Detected in Patients With Non-Obstructive Azoospermia and Oligozoospermia

Abstract: Genetic factors have a major importance in male infertility etiology. Numerical and structural chromosomal abnormalities seem to be frequent inoligospermia and azoospermia cases with unknown etiology. In this study, 819 patients with azoospermia (383) and oligospermia (436) who attended the infertility department between 1995-2005 were evaluated. Spermogram and basic hormone proties (FSH-testosterone) were studied two times in a one month interval from each patient, and all the cases were evaluated cytogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
4
16
0
3
Order By: Relevance
“…Among gonosomal chromosomal anomalies 1.12% was structural and 2.68% was numerical whereas those values were 1.11% and 8.93% in our study. Comparison of our results with the review of the literature shows a relatively higher incidence of gonosomal, in particular, numerical gonosomal, chromosomal anomalies in our center which is similar to the literature reporting on Turkey [7,16]. Although our results reflect a regional pattern of those referrals, combined with the previous results from Turkey, further studies focusing on this issue may be suggested to clarify this relatively higher incidence.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Among gonosomal chromosomal anomalies 1.12% was structural and 2.68% was numerical whereas those values were 1.11% and 8.93% in our study. Comparison of our results with the review of the literature shows a relatively higher incidence of gonosomal, in particular, numerical gonosomal, chromosomal anomalies in our center which is similar to the literature reporting on Turkey [7,16]. Although our results reflect a regional pattern of those referrals, combined with the previous results from Turkey, further studies focusing on this issue may be suggested to clarify this relatively higher incidence.…”
Section: Discussionsupporting
confidence: 70%
“…Evaluation of 15 similar studies from the literature including a total of 9374 cases showed 6.54% chromosomal anomaly rate (Table 3) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In our study 11.74% of all cases revealed chromosomal alteration including inv (9).…”
Section: Discussionmentioning
confidence: 73%
“…Akgül et al found that chromosomal abnormalities were detected in 17.4% of 86 azoospermic cases and in 6.8% of 73 oligozoospermic cases in a regional study in Turkey [2]. Samli et al reported chromosomal abnormality in 47 (12%) of 383 non-obstructive azoospermia cases and in 20 (4%) of 436 oligospermic patients [34]. More recently, chromosomal abnormalities were detected in 5.4% of 92 azoospermic cases and no patients of 23 oligozoospermic cases [32] ( Table 4).…”
Section: Discussionmentioning
confidence: 95%
“…There are some other cytogenetic studies conducted on infertile patients from different part of Turkey [29][30][31]. Akgül et al have found that chromosomal abnormalities were detected in 17.4% of 86 azoospermic cases and 6.8% of 73 oligozoospermic cases revealed 11.7% of all cases in a regional study from Turkey.…”
Section: Discussionmentioning
confidence: 99%